Pseudo-Memoirs : Life and Its Imitation in Modern Fiction - Tobias, Rochelle, 1963- (Book collections on Project MUSE., 2021)
"Pseudo-Memoir explores the twentieth-century return of a genre that had largely gone out of fashion after the novel came of age in Europe in the eighteenth century"--